2012
DOI: 10.3354/meps09630
|View full text |Cite
|
Sign up to set email alerts
|

Swimming patterns of wild harbour porpoises Phocoena phocoena show detection and avoidance of gillnets at very long ranges

Abstract: Harbour porpoises Phocoena phocoena are unintentionally caught in gillnets. Although the effectiveness of by-catch mitigation measures has been evaluated many times, only a few studies have investigated the behavioural patterns of the porpoises in relation to the presence of fishing nets. In this study, the reactions of wild harbour porpoises to a modified gillnet were visually observed. The porpoises responded to the net by avoiding it, with reactions being detectable at a distance of >80 m. The number of ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
2
15
0
Order By: Relevance
“…It has been suggested that porpoises may be capable of detecting fishing nets at distances of up to 80 m (Nielsen et al 2012; but see Dawson & Lusseau 2013, Nielsen et al 2013. If porpoises are able to detect gillnets up to 80 m away, it may only be relevant to alert them to a net within this range if they are preoccupied e.g.…”
Section: Habitat Displacementmentioning
confidence: 99%
“…It has been suggested that porpoises may be capable of detecting fishing nets at distances of up to 80 m (Nielsen et al 2012; but see Dawson & Lusseau 2013, Nielsen et al 2013. If porpoises are able to detect gillnets up to 80 m away, it may only be relevant to alert them to a net within this range if they are preoccupied e.g.…”
Section: Habitat Displacementmentioning
confidence: 99%
“…Wild porpoises have since been recorded producing SLs up to 30 dB greater than those of captive animals; therefore, the estimated potential detection range of gillnets by this species was increased to around 13 to 26 m (Villadsgaard et al 2007). More recently, a study has shown that free-ranging harbour porpoises detect and avoid gillnets at distances up to 80 m (Nielsen et al 2012); distances at which the small increase in TS provided by acoustically reflective nets is unlikely to have much influence. Additionally, Cox & Read (2004) found no difference in echolocation rate or echolocation intensity of harbour porpoises around BaSO 4 gillnets compared to around standard gillnets, indicating that porpoises did not change their echolocation behaviour in response to the reflective net.…”
mentioning
confidence: 99%
“…Pingers have been reported to deter harbour porpoises from nets (Cox et al, 2001;Culik et al, 2001) and to efficiently reduce bycatch (Kraus et al, 1997;Larsen et al, 2013). Although previous studies indicate that harbour porpoises can detect gill nets at sufficient distance to avoid them (Kastelein et al, 2000;Koschinski et al, 2006;Villadsgaard et al, 2007;Nielsen et al, 2012), for unknown reasons they are still being caught in nets both with and without pingers (Dawson et al, 1998). In addition, there may be several potential problems with a large-scale use of pingers such as habituation and noise pollution.…”
mentioning
confidence: 99%
“…Given the source level and propagation loss of harbour porpoise echolocation clicks (e.g., Villadsgaard et al, 2007) and the detection threshold of the data loggers (around 140 dB re 1 µPa p), the loggers can pick up these signals at a range of several hundreds of meters. Harbour porpoises are able to detect fishing gear at somewhat shorter, but still comparable, ranges (presumably using acoustic cues; see Nielsen et al, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation